PERAN DAN POSISI PUBLIC RELATIONS DALAM HOSPITALITY INDUSTRY - Tandiyo Pradekso; Yanuar Luqman; Taufik Suprihatini (JURNAL ILMU SOSIAL, 2013)
The role of public relations in hospitality industry had been significantly increasing along with the rapid growth of the industry. A study of the issue in 2 respective hospitals and a hotel indicates that each had set a different level of position within the management. Regardless to the type of the organization, public relations with the higher level of position had a better access to resources and decision making, which consecutively put them as expert prescriber. Converssely, a stumpy management value had dispose public relations as a merely communication techni  cian. Organizational culture and communication climate were considered as determinants to how the management perceives public relations.